2018
DOI: 10.1002/cpdd.438
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Safety of Bazedoxifene in Hepatically Impaired and Healthy Postmenopausal Women

Abstract: Bazedoxifene, a selective estrogen receptor modulator with proestrogenic effects on bone and lipid metabolism and antiestrogenic effects on the breast and endometrium, is a treatment option for osteoporosis in postmenopausal women. It is extensively metabolized by the liver; therefore, a decrease in liver function was expected to decrease bazedoxifene clearance. This single-dose, open-label, inpatient/outpatient, nonrandomized study assessed the pharmacokinetics of bazedoxifene 20 mg in 18 postmenopausal women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Bazedoxifene and ibuprofen bioanalytical assays were performed by CEPHAC (Saint‐Benôit Cedex, France). Plasma samples were measured for bazedoxifene using a previously described, validated high‐performance liquid chromatography (HPLC) method with fluorescence detection, with a limit of quantification of 25 pg/mL . The intrabatch precision based on the coefficient of variation (%CV) ranged from 1.19% to 3.95%, and the percentage of bias, defined as the percentage difference between measured and theoretical concentrations, ranged from −7.82% to 16.37%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bazedoxifene and ibuprofen bioanalytical assays were performed by CEPHAC (Saint‐Benôit Cedex, France). Plasma samples were measured for bazedoxifene using a previously described, validated high‐performance liquid chromatography (HPLC) method with fluorescence detection, with a limit of quantification of 25 pg/mL . The intrabatch precision based on the coefficient of variation (%CV) ranged from 1.19% to 3.95%, and the percentage of bias, defined as the percentage difference between measured and theoretical concentrations, ranged from −7.82% to 16.37%.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma samples were measured for bazedoxifene using a previously described, validated high-performance liquid chromatography (HPLC) method with fluorescence detection, with a limit of quantification of 25 pg/mL. 21 The intrabatch precision based on the coefficient of variation (%CV) ranged from 1.19% to 3.95%, and the percentage of bias, defined as the percentage difference between measured and theoretical concentrations, ranged from −7.82% to 16.37%. The interbatch precision (%CV) of the bazedoxifene assay ranged from 3.88% to 4.96%, and the percentage of bias ranged from −12.35% to 14.52%.…”
Section: Bioanalytical Assaysmentioning
confidence: 99%
“…Plasma bazedoxifene concentrations were measured using a previously described, validated high‐performance liquid chromatography (HPLC) method with fluorescence detection …”
Section: Methodsmentioning
confidence: 99%
“…Plasma bazedoxifene concentrations were measured using a previously described, validated high-performance liquid chromatography (HPLC) method with fluorescence detection. 24 As approximately 70% of circulating inhibitory activity for HMG-CoA reductase is attributed to active metabolites, the 2 major active metabolites (orthohydroxylated and para-hydroxylated atorvastatin) were assayed in addition to the parent atorvastatin compound using HPLC with mass spectrometric detection. Atorvastatin, para-hydroxyatorvastatin, and orthohydroxyatorvastatin and their respective internal standards (D 5 -atorvastatin, D 5 -para-hydroxyatorvastatin, and D 5 -ortho-hydroxyatorvastatin) were extracted from plasma samples using solid-phase extraction.…”
Section: Assay Methodsmentioning
confidence: 99%
“…As BZA is conjugated by hepatic and intestinal enzymes, it seems that both hepatic and extrahepatic metabolism play a role in clearance and disposition . A single‐dose study in postmenopausal women with hepatic impairment showed that apparent oral dose clearance (CL/F) was lower and t ½ longer than for those with normal hepatic function …”
mentioning
confidence: 99%